2015
DOI: 10.1007/978-94-017-9939-3_61
|View full text |Cite
|
Sign up to set email alerts
|

Various Durability Aspects of Calcined Kaolin-Blended Portland Cement Pastes and Concretes

Abstract: The use of calcined clay, in the form of metakaolin (MK), as a pozzolanic constituent for concrete has received considerable attention in recent years, due to the lower CO 2 emission of this supplementary cementitious material compared to the production of a classic portland cement. Furthermore, concretes incorporating MK show some improve durability properties. In this paper, the durability of concretes and cement pastes with MK as partial replacement of cement (10 and 25 %) has been investigated in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…Consequently, it is not obvious to understand why ettringite would be more stable than AFm phases in these conditions. Moreover, it is well known that AFm phases can react with carbonates (CO3 2-) to form monocarboaluminates [4], [36][37][38][39]. However, in the present study, XRD showed no ettringite or monocarboaluminate in TC samples in comparison to Ref samples (figure 6).…”
Section: Chemistry Of Alumina Phasescontrasting
confidence: 70%
See 1 more Smart Citation
“…Consequently, it is not obvious to understand why ettringite would be more stable than AFm phases in these conditions. Moreover, it is well known that AFm phases can react with carbonates (CO3 2-) to form monocarboaluminates [4], [36][37][38][39]. However, in the present study, XRD showed no ettringite or monocarboaluminate in TC samples in comparison to Ref samples (figure 6).…”
Section: Chemistry Of Alumina Phasescontrasting
confidence: 70%
“…When polymerizing, the C-S-H chains release water and this water is probably evaporated during the time in carbonation chamber (RH 65% and T=20°C). Consequently, there is probably a coupling effect between carbonation and drying as reported [39,40] and it will be discussed in the following section. 29 Si NMR.…”
Section: Modifications Of C-as-h After Carbonationmentioning
confidence: 94%
“…[44] also associated the phenomenon with the metakaolin pozzolanic reaction, which consumed CH responsible for slowing the carbonation rate. A similar argument was provided by Saillio et al [45], who showed a trend of CH decrease and carbonation depth increase with increasing metakaolin content and exposure time.…”
Section: Carbonationsupporting
confidence: 82%
“…Quite a large group of papers on durability are focused on cement systems with calcined kaolin. Saillio et al [ 202 ], as well as Yazıcı [ 203 ], have analysed various aspects of the durability of concrete and mortars produced with metakaolin addition. Tafraoui et al [ 204 ] gave a brief literature review on the durability of ultra-high performance concrete containing metakaolin.…”
Section: Influence Of Calcined Clay On the Durability Of Concretementioning
confidence: 99%